2017
DOI: 10.1016/j.brat.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

How durable is the effect of low intensity CBT for depression and anxiety? Remission and relapse in a longitudinal cohort study

Abstract: Background: Depression and anxiety disorders are relapse-prone conditions, even after successful treatment with pharmacotherapy or psychotherapy. Cognitive behavioural therapy (CBT) is known to prevent relapse, but there is little evidence of the durability of remission after low intensity forms of CBT (LiCBT).Method: This study aimed to examine relapse rates 12 months after completing routinely-delivered LiCBT. A cohort of 439 LiCBT completers with remission of symptoms provided monthly depression (PHQ-9) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 45 publications
(57 reference statements)
5
88
3
1
Order By: Relevance
“…117 critical period where the majority (2 out of 3) of relapse-prone cases become apparent. Consistent with earlier studies, we have previously reported that patients who completed therapy with residual depression symptoms (PHQ-9 = 5-9) had double the risk of relapse within the first year [12].…”
supporting
confidence: 79%
See 1 more Smart Citation
“…117 critical period where the majority (2 out of 3) of relapse-prone cases become apparent. Consistent with earlier studies, we have previously reported that patients who completed therapy with residual depression symptoms (PHQ-9 = 5-9) had double the risk of relapse within the first year [12].…”
supporting
confidence: 79%
“…Mean pre-and post-treatment measures were PHQ-9 = 13.60 (SD = 5.41) and 3.44 (SD = 2.40), respectively, and GAD-7 = 13.20 (SD = 4.38) and 3.19 (SD = 2.17). Full details about recruitment, inclusion criteria, and methods can be found in a preliminary report of 12-month outcomes [12]. The study was approved by the NHS Health Research Authority (Yorkshire and Humber REC; Ref.…”
mentioning
confidence: 99%
“…While shorter assessment techniques might help achieve the access rate targets, it is necessary to recall research which reports moderate rates of re‐referral (Cairns, ; Hepgul et al, ) and relapse (Ali et al, ) as well as poor to variable rates of stepping‐up (Clark et al, ; Delgadillo et al, ; Glover et al, ; Richards et al, ), and treatment allocation practices (Bower et al, ; Chan & Adams, ; Goddard et al, ; Hepgul et al, ) within IAPT services. Other factors are of equal importance alongside the drive to increase access volume, including converting referrals from entering to completing treatment, securing representative data and enhancing session attendance (Clark et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While this is not necessarily indicative of a negative outcome, it is notable that almost half are discharged having attended one session only (IAPT, ; Richards & Borglin, ). Other evidence finds wide variability in stepped‐care modelling between services (Clark et al, ; Glover et al, ; Richards et al, ), little discrimination in condition severity between low‐ and high‐intensity interventions (Bower et al, ; Chan & Adams, ), highly complex cases including those with personality disorders being referred, assessed and treated (Goddard, Wingrove, & Moran, ; Hepgul et al, ), poor to variable rates of stepping‐up (Clark et al, ; Delgadillo, Gellatly, & Stephenson‐Bellwood, ; Richards et al, ), moderate rates of re‐referral (Cairns, ; Hepgul et al, ) and poor durability of low‐intensity treatments beyond 1 year (Ali et al, ). These findings suggest that referrals might not be receiving adequate treatment initially or during the course of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the programme have also been queried, with some claiming that the true costs of the programme have been underestimated and the positive outcomes inflated (Griffiths & Steen, , ). Indeed, about half of low‐intensity therapy patients relapse, most within six months of the end of treatment (Ali et al ., ). Despite these misgivings, the IAPT programme has become firmly established within the NHS and has an ever widening remit that now includes children, people with long‐term conditions and medically unexplained symptoms.…”
Section: Low‐intensity Cbtmentioning
confidence: 99%